CHARACTER BASED INTERACTIVE MULTIMEDIA IN WRITING SHORTSTORY CLASS FOR PRIMARY SCHOOL GRADE 6 - Cerianing Putri Pratiwi; Fauzatul Ma’rufah Rohmanurmeta (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
The purpose of this study is to find out the application of character-based interactive multimedia in learning to write short stories for primary school grade 6. The type of this research is qualitative descriptive. This study has verbal data, namely the results of recording character-based interactive multimedia implementation activities on learning to write short stories for primary school grade 6. Nonverbal data in this study is the value of the evaluation of students' short story writing skills. Subjects in this study were teachers and students of grade 6 primary school. This study uses data collection techniques, namely (a) observation, (b) interviews, and (c) tests, (d) documentation. The technique used to analyze data analysis data is interactive data analysis techniques. There are three stages (a) data reduction, (b) data presentation, and (c) conclusion. The application of character-based interactive multimedia has been implemented in accordance with the plans that have been made by the teacher as outlined in the Learning Implementation Plan. Based on the results of the evaluations that have been given, the short story writing skills of primary school grade 6 are good enough. This was seen in the average writing value of 78.3% of 15 students. There were 5 students who received a score of 70. There were 5 students who scored 80, while the other 5 students got a score of 85. Minimum completeness criteria for Indonesian language study were 75. It showed that there were 5 students who had not yet completed or 33.3%, while students who have completed there are 10 students or as much as 66.7%